Analysis of programs for ensuring active longevity of persons of older age groups in the moscow region - N. I. Burdaev; S. G. Sboeva; S. A. Krivosheev (Сеченовский вестник, 2019)
Aim. To study non - stationary and semi - stationary forms of health - improving services of multifunctional regional social welfare centers and determine satisfaction with their quality. Material and methods. The annual reports of state budgetary institutions of Territorial Centers for Social Welfare for 2017, projects to ensure healthy longevity. A survey of 210 respondents was conducted (average age - 71 years) of the participants in the Moscow Longevity project about satisfaction with the provision of recreational services of Territorial Centers for Social Welfare. Statistical analysis included the study of the absolute and relative values of the indicators obtained. Results. An analysis of the activities of 6 organizations of the Moscow Territorial Centers for Social Welfare revealed the implementation of all federal and regional programs, as well as two of them - local projects to stimulate active longevity. Women (68%) and persons with a higher education (48%) prevailed among the surveyed participants in the Moscow Longevity project. The frequency of chronic diseases and the attendance of medical care increased with age of the respondents. The average cost of purchasing drugs amounted to 25% of the monthly pension. Within one to three years, 54% of respondents used the services of Territorial Centers for Social Welfare. The analysis of satisfaction with the quality of social and health services showed high rates (4.7-4.9 points out of 5) for the criteria “Goodwill and competence of employees”, “Organization of educational, physical, leisure and social and cultural activity”. Average values (4.5-4.6 points) were obtained for the criteria “Openness and availability of information about the services provided” and “Comfort of conditions for the provision of services”. The lowest number of points - 4.2 - was obtained according to the criterion "Organization of medical and pharmaceutical care". Conclusions. In addition to federal and regional programs, organizations of the Moscow Territorial Centers for Social Welfare also implement local projects to stimulate active longevity. The majority of respondents use the services of Territorial Centers for Social Welfare for more than one year and positively evaluate their activities, but consider it expedient to increase the semi - stationary and non - stationary bases of the Territorial Centers for Social Welfare, create conditions for the provision of medical and medicinal care.